Determinants of donor generosity: a survey of the aid budget literature - Fuchs, Andreas; Dreher, Axel; Nunnenkamp, Peter (World development, 2014)
This article provides a survey of the aid budget literature and examines the determinants of the development aid efforts of 22 Development Assistance Committee (DAC) members over the 1976-2011 period. In fixed effects regressions, we identify aid inertia, per-capita GDP, the creation of an independent aid agency, colonial history, Russian military capacity, peer effects, terror incidents, aid to CEEC/NIS countries, and imports from developing countries as determinants of the Official Development Assistance (ODA)-to-GNI ratio. Excluding donor fixed effects, several variables, including colonial history and the aid agency dummy, are no longer significant; the impact of per-capita GDP gets weaker, while donors’ budget deficits decrease aid effort.
Available online 3 December 2013
Gesehen am 28.08.2020